Commodity Traders in a Storm: Financialization, Corporate Power and Ecological Crisis - Joseph Baines; Sandy Brian Hager (Review of International Political Economy, 2021)
Commodity trading firms occupy a central position in global supply chains and their activities have been associated with financial instability, social upheaval and manifold forms of ecological devastation. This paper examines these companies in the context of debates regarding corporate financialization. We find that since the 2003–2011 commodity boom, trading firms have become less financialized in terms of the source of their profits as they have shifted away from financial activities. However, they have become more financialized in terms of the destination of profits, with dividend and share repurchase commitments reaching new heights after 2015. In view of this finding, we inquire into whether trading firms' growing commitment to shareholder payouts will encourage them to continue to prioritize short-term returns, or whether instead these firms' linkages to financial markets will lend clout to financial activists concerned by the long-term environmental and social consequences of their operations. Ultimately, we find several sources of commodity trader resilience which insulate them from shareholder resolutions and divestment campaigns aimed at curbing ecological destruction and human rights abuses in their supply chains. We accordingly suggest that pressures from activist investors must be complemented with more wide-ranging efforts to defend living systems across the planet.
Keywords: P16; G3; L66; G; 330; commodities; corporation; crisis; ecology; finance; power; valuation